In the wake : on Blackness and being - Sharpe, Christina Elizabeth (Anti-racist collection, 2016)
Using the multiple meanings of "wake" to illustrate the ways Black lives are determined by slavery's afterlives, Christina Sharpe weaves personal experiences with readings of literary and artistic representations of Black life and death to examine what survives in the face of insistent violence and the possibilities for resistance.